Investigating the Effectiveness of BU WebEx System - Krainuyachan, Payon; Choensawat*, Worawat; Isarakorn, Don (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Nowadays, distant-learning systems provide a wide range of learning techniques with flexibility that provide students with increased opportunities, convenience, and personalization. In the 21st century, students can choose their own studying style whether learning at home or the university. Students can learn at home without the physical presence of a teacher. Recently, Thailand has experienced the worst flooding in over 50 years. At that time, some students and teachers had difficulty in commuting. For that reason, Bangkok University adopted a “BU WebEx” system which designed for helping teachers and students for distant learning. So far, there is little research have been conducted on the effectiveness of distant learning. In this study, we analyzed and described how students and teachers participated in the BU WebEx system. We examined the students’ participation rates, the network connection, and the amount of spending time. The data consist of log files of the BU WebEx system and user’s feedbacks after using the system. Keywords: WebEx System, Distance Learning, Virtual Classroom, Effectiveness Evaluation. Email: worawat.c@bu.ac.th